2008
DOI: 10.1124/mol.107.041053
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Assay of Gi/o-Linked G Protein-Coupled Receptor Coupling to Potassium Channels Provides New Insights into the Pharmacology of the Group III Metabotropic Glutamate Receptors

Abstract: The group III metabotropic glutamate receptors (mGluRs) represent a family of presynaptically expressed G-protein-coupled receptors (GPCRs) with enormous therapeutic potential; however, robust cellular assays to study their function have been difficult to develop. We present here a new assay, compatible with traditional high-throughput screening platforms, to detect activity of pharmacological ligands interacting with G i/o -coupled GPCRs, including the group III mGluRs 4, 7, and 8. The assay takes advantage o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
146
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 103 publications
(148 citation statements)
references
References 38 publications
2
146
0
Order By: Relevance
“…HEK-293 cells coexpressing human GIRK1/2 and rat mGlu 8 were generated as previously described. 25 A HEK-293 cell line (ATCC, Manassas, VA) expressing human GIRK1 and human GIRK2 was constructed by transfecting HEK-293 cells with GIRK1 and GIRK2 (Origene, Rockville, MD) cloned into the pBudCE4.1 vector (Life Technologies, Carlsbad, CA) using FuGene 6 (Promega, Madison, WI) transfection reagent. Unless otherwise noted, other ion channel-expressing cells were prepared by transfecting HEK-293 cells with individual or combinations of subunits: GIRK1, pCMV6-A-BSD; GIRK2, pCMV6-A-puro; GIRK3, pCMV6-A-hygro; GIRK 4, pCMV6-A-AC; Kv7.4, pIRESneo3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…HEK-293 cells coexpressing human GIRK1/2 and rat mGlu 8 were generated as previously described. 25 A HEK-293 cell line (ATCC, Manassas, VA) expressing human GIRK1 and human GIRK2 was constructed by transfecting HEK-293 cells with GIRK1 and GIRK2 (Origene, Rockville, MD) cloned into the pBudCE4.1 vector (Life Technologies, Carlsbad, CA) using FuGene 6 (Promega, Madison, WI) transfection reagent. Unless otherwise noted, other ion channel-expressing cells were prepared by transfecting HEK-293 cells with individual or combinations of subunits: GIRK1, pCMV6-A-BSD; GIRK2, pCMV6-A-puro; GIRK3, pCMV6-A-hygro; GIRK 4, pCMV6-A-AC; Kv7.4, pIRESneo3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…We utilized this methodology following the protocol of the Delpire group (21), since they and other groups have shown similar results between 86 Rb and FluxOR. This method uses TI ϩ as a surrogate of K ϩ , and a TI ϩ -sensitive fluorescent dye (Flix-ORTM) to visualize TI ϩ uptake through NKCC1 in single cells (27,38,59). We found that addition of ALD to the media resulted in a marked increase in fluorescence of NKCC1 with both the 86 Rb and Tl ϩ methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…11,27 Nevertheless, the potential of this assay to quickly test multiple agonists or putative modulators of receptor desensitization in an intact system makes it an attractive option. GIRK channel activation has most commonly been assessed using electrophysiological techniques, but assays potentially suitable for HTS have been reported using thallium flux 29 or commercially available membrane potential dyes. 30,31 Thallium is toxic and apparently unsuitable for all cell lines, 31 whereas other membrane potential sensitive dyes (Di-Bac, HLB 021-152) give results qualitatively similar to those reported here.…”
Section: Discussionmentioning
confidence: 99%